An Ecofeminist Reading of Hadestown: The Myth, The Muscial - Vos, Abigail (University of the Witwatersrand, Johannesburg, 2023)
Hadestown: The Myth, the Musical has merged two ancient love stories and has presented these stories within a world riddled with environmental damage. The four main characters (Orpheus, Eurydice, Persephone, and Hades) are influenced by the environment in various ways. Persephone acts as the goddess of the natural world and therefore is nature’s ambassador. Hades, the king of the Underworld, has become an industrial mogul and has inadvertently damaged the earth with his industrial kingdom. As a result, Eurydice is left to suffer these consequences and faces poverty and hunger because of the environmental imbalance that engulfs her. Orpheus, in response, attempts to write a song that will bring balance to the world once more. Our characters are situated within an environmentalist fable; therefore, the musical’s narrative centres around how these characters interact with the environment. The music of Hadestown has been carefully selected in an eclectic way. Jazz, folk, musical theatre, and opera have all had various influences on the musical world of the show. This influence is not simply limited to the score, but the histories of these genres bleed into the work. Folk and jazz both carry profound messages of struggle and protest with them, and therefore the use of these genres aids in the environmentalist activism presented in the musical. These genres and their social and geographical histories are layered into Hadestown. The musical allows for deep character analysis and textual analysis through the writing of Anaïs Mitchell. In this research, I will present an analysis of the lyrics of Hadestown to present the embedded themes of environmentalism, anti-capitalism, and anti-industrialism. My analysis will present how the pained Earth and Her inhabitants reflect the pain endured by the Global South, specifically by women. Impoverished women in third-world countries face most environmental consequences accompanying the Global North’s incessant need for more. This effect is portrayed in the lives of Eurydice and Persephone. An ecofeminist framework will be applied to the work as Persephone exhibits inherent ecofeminist traits. Hadestown presents its audience with a mirror of the world they live in and ask its audience what it will do about it.
A research report submitted in partial fulfillment of the requirements for the degree of Master of Arts in Music, to the Faculty of Humanities, Wits School of Arts, University of the Witwatersrand, Johannesburg, 2023
Keywords: Ecofeminism; Hadestown; Musical theatre; Anti-capitalism; Anti-industrialism; Environmentalism; Feminism; UCTD; SDG-4: Quality education